The Use of Padlet Application to Teach Writing in Hybrid Learning: A Reflection of Online Teaching in Pandemic Era - Nafik, Aulia An (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Technology plays a role in supporting language learning. This is especially important in the current situation where physical meetings and face-to-face learning processes cannot be performed optimally due to some health protocol rules. The effectiveness of technical tools depends on the experience and knowledge of the teacher who applies or uses them to facilitate the flow of the teaching-learning process. Today, some many tools and applications help teachers support the teaching and learning process. One of them is the Padlet application. This paper is reflection of the use of Padlet application in a hybrid teaching-learning process during the second semester of academic year 2021/2022. The paper aims to explain students' perception regarding the implementation of hybrid learning and the use of this web application to support the teaching-learning process, specifically teaching writing skill for the first-year university students. The writer observed two classes of Basic Writing for communication science students of a private university in Semarang. Students' responses to a questionnaire were used to find out the student's reflections on the use of the application during the hybrid learning process. The finding showed that Padlet is very useful to teach writing in hybrid learning. It can facilitate students to work collaboratively and enhance students' engagement in writing activities.